2020
DOI: 10.3390/biom10010143
|View full text |Cite
|
Sign up to set email alerts
|

Synthetically Lethal Interactions of Heme Oxygenase-1 and Fumarate Hydratase Genes

Abstract: Elevated expression of heme oxygenase-1 (HO-1, encoded by HMOX1) is observed in various types of tumors. Hence, it is suggested that HO-1 may serve as a potential target in anticancer therapies. A novel approach to inhibit HO-1 is related to the synthetic lethality of this enzyme and fumarate hydratase (FH). In the current study, we aimed to validate the effect of genetic and pharmacological inhibition of HO-1 in cells isolated from patients suffering from hereditary leiomyomatosis and renal cell carcinoma (HL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 37 publications
0
14
0
Order By: Relevance
“…The authors show that when heme synthesis was upregulated, it led to incorporation of radiolabeled fumarate into heme via succinate and succinyl-CoA [ 20 ]. More recently it has been shown that fumarate hydratase (FH) and HO-1 are synthetically lethal [ 26 , 27 ]. FH deficient cells accumulated fumarate and succinate and had increased expression of HO-1.…”
Section: Resultsmentioning
confidence: 99%
“…The authors show that when heme synthesis was upregulated, it led to incorporation of radiolabeled fumarate into heme via succinate and succinyl-CoA [ 20 ]. More recently it has been shown that fumarate hydratase (FH) and HO-1 are synthetically lethal [ 26 , 27 ]. FH deficient cells accumulated fumarate and succinate and had increased expression of HO-1.…”
Section: Resultsmentioning
confidence: 99%
“…Numerous studies have proved that the anti-inflammatory, antioxidant, pro-angiogenic, anti-thrombotic, and anti-apoptotic effects of HO-1 are derived from its catabolic byproducts, CO and biliverdin, which render HO-1 as a tissue protector and a good candidate for investigating new therapeutic interventions [1,8,13]. However, several studies have extensively demonstrated the positive role of HO-1 in cancer progress [14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, we investigated whether brazilin-induced HO-1 expression, but it was not observed (data not shown). Moreover, novel HO-1 inhibition tools were reported such as arylethanolimidazole derivatives in cancer [ 49 ], caffeic acid phenethyl ester in diabetes [ 50 ] and fumarate hydratase as target genes in cancer [ 51 ].…”
Section: Discussionmentioning
confidence: 99%